THE ELECTORAL BONDS DILEMMA: BALANCING POLITICAL FUNDING WITH ELECTION FAIRNESS - Sinha, Anju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of electoral bonds offers a difficult conundrum at the junction of fair elections and political finance openness. Originally meant to simplify political contributions in India, electoral bonds enable supporters of political parties to remain anonymous, therefore presumably lowering uncontrolled cash flow. Proponents of this financing strategy claim it allows a simpler, more direct approach for donations without violating donor privacy, which may be particularly important in a politically sensitive climate that has polarizing public opinion. Critics counter that by letting unreported sums into political campaigns, it lessens democratic responsibility and shifts the balances in favor of those with more financial support.